A Real-time EMF Measuring System for Mobile Communication Towers in Sri Lanka - Lakshitha Rangana, WICKRAMASINGHE; Sisaara , PERERA (Instrumentation, 2021)
Telecommunications Regulatory Commission of Sri Lanka is the governing body which is responsible for the frequency allocation and monitoring the unauthorized Electromagnetic frequency (EMF) signal transmitting violations. However, in Sri Lanka, currently there is not any proper mechanism to monitor the radiation hazard level and its impact to the people living in the vicinity of mobile communication towers. There are approximately 7000 mobile transmitting towers in Sri Lanka to date and the used frequency range lies between 900MHz to 3GHz for mobile communication. Over the last few decades, many of the health hazard conditions were reported due to the radiation of those harmful EMFs. To cater this problem, a portable real time EMF signal strength measuring system with a radiation hazard level indicator was developed to monitor the EMF level and its impact. The proposed system operates with three intermediate frequency bands (i.e.900MHz, 1800 MHz and 2400MHz) and it’s capable of measuring the power density and the radiation hazard level at that particular point which is being measured. Moreover, the corresponding radiation hazard level is indicated with reference to the standard power density levels published by the International Commission on Non-Ionizing Ra-diation Protection (ICNIRP*). The system works with the overall accuracy of 88% in terms of identifying the power densities and its corresponding radiation hazard levels.